Analysis of Agile Concept Application in Lectures Conduction at UTM Jakarta and STIKOM CKI - Miswanto; Romadloni, Nova Tri (Program Studi Pendidikan Teknologi Infromasi UMK, 2024)
In today’s fast-paced tech world, it’s important to understand and adapt to new methods like Agile. Agile is commonly used in project and product management to help with planning, executing, monitoring, and completing projects based on user needs. This approach can also be applied in education, especially in classroom lectures. This research examines how Agile is used in lectures at UTM Jakarta and STIKOM CKI Jakarta. It looks at students’ understanding of Agile, their creativity during lectures, and the impact of a new curriculum on classroom learning. To analyse this, the study used descriptive statistics to measure students' understanding of Agile, a correlation test to see connections between different aspects of lectures, and a regression test to examine the new curriculum's impact. The goals are to 1) Measure students' understanding of Agile concepts. 2) Assess students' creativity in class, and 3) Analyze how curriculum changes affect classroom activities. Results show that students have a moderate understanding of Agile, and their creativity is evident in how they apply concepts, document work, and present material. The regression model shows that the new curriculum has a positive impact on classroom learning, and the findings are valid and reliable. Overall, Agile methods can enhance learning and creativity in the classroom.